A Compact Highly Isolated Four-Element Antenna System for Ultra-Wideband Applications - V. Prithivirajan; Mariya Princy Antony Saviour; J. Seetha; B. Siva Kumar Reddy; Anand Anbalagan; D. Rajesh Kumar (International Journal of Antennas and Propagation)
A small, orthogonally polarized, ultra-wideband (UWB), four-port multiple-input multiple-output (MIMO) printed antenna is presented in this study. The envisioned antenna is built up of four microstrip fractal-based circular patch elements, each of which is fed by a microstrip line with a 50-ohm impedance. The use of a defective ground plane allows for the ultra-wideband frequency response to be obtained. In order to achieve maximal isolation, the amount of surface current that flow between the antenna’s four components is limited by arranging radiating elements orthogonally. The four-port MIMO system is printed on a FR4 substrate with a loss tangent of 0.02 and an overall dimension of 20 × 30 × 1.6 mm3. A port-to-port isolation of less than 25 dB was achieved as a consequence of this orthogonal orientation of antenna elements, and the impedance bandwidth is achieved up to 158% (3.1–12 GHz). The suggested ultra-wideband multiple-input multiple-output (UWB-MIMO) antenna achieved a maximum gain of 8 dBi over the operational frequency range (3.1–12 GHz); the findings that were measured and those that were simulated accord with one another rather well. The findings also give an overall strong diversity performance, with the ECC < 0.25, DG > 9.9, and CCL < 0.2 values all being within acceptable ranges.